Credit cards: Facts and theories - Carol C. Bertaut; Michael Haliassos (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
We use data from several waves of the Survey of Consumer Finances to document credit and debit card ownership and use across US demographic groups. We then present recent theoretical and empirical contributions to the study of credit and debit card behavior. Utilization rates of credit lines and portfolios of card holders present several puzzles. Credit line increases initiated by banks lead households to restore previous utilization rates. High-interest credit card debt co-exists with substantial holdings of low-interest liquid assets and with accumulation of retirement assets. Although available evidence disputes ignorance of credit card terms by card holders, credit card rates do not respond to competition. There is a rising trend in bankruptcy and delinquency, partly attributable to an increased tendency of households to declare bankruptcy associated with reduced social stigma, ease of procedures, and financial incentives. Co-existence of credit card debt with retirement assets can be explained through self-control hyperbolic discounting. Strategic default motives contribute partly to observed co-existence of credit card debt with low-interest liquid assets. A framework of 'accountant-shopper' households, in which a rational accountant tries to control an impulsive shopper, seems consistent with both types of co-existence and with observed utilization of credit lines.
urn:nbn:de:hebis:30-33257
Keywords: G11; E21; 330; Credit Cards; Debit Cards; Revolving Debt; Consumer Credit; Portfolios; Kreditkarte; Verbraucherkredit; USA; Kreditkarte; Verbraucherkredit; USA